An epidemiological study of malocclusion and occlusal traits related to different stages of dental development - Redzepagic Vrazalica, Lejla; Ilic, Zlatko; Laganin, Slaven; Dzemidzic, Vildana; Tiro, Alisa (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Various types of malocclusions present one of the most common dental problems of today’s population. Planning the implementation of orthodontic therapy, especially preventive and interceptive measures is one of many activities of public sector health, and it requires information regarding the prevalence of malocclusion in different parts of our country.The aim: The aim of this study was to determine the prevalence of malocclusion of preschool and school children in the city of Sarajevo.Materials and methods: This study was comprised of 373 children out of which 200 preschool and school children were included in the final sample according to the inclusion and exclusion criteria for participation. 100 children were five-year-olds with complete deciduous dentition, and 100 children were 14-year-olds with permanent dentition. The examined variables in the study were: dental status andexistence of caries, overjet, depth of overbite, a presence of premature contacts, a presence of diastemas, crowding of teeth in the dentalarch (for 14-year-olds) and rotation of teeth in the dental arch (for 14-year-olds).Results: The prevalence of malocclusion was 58% in the group of preschool children and 83% in the group of school children.Conclusion: Results of this study demonstrate a need for the implementation of preventive and interceptive orthodontic methods inprimary health care, which would reduce the need for expensive and long term orthodontic therapy.